A point mutation in the zinc-finger transcription factor CqLOL1 controls the green flesh color in chieh-qua (Benincasa hispida Cogn. var. Chieh-qua How) - Peng, Jiazhu; Gao, Yin; Qiao, Yanchun; Wang, Guoping (Frontiers in plant science, 2024)
Flesh color is an essential trait in chieh-qua ( Cogn. var. How); however, the inheritance and molecular basis of green flesh trait remain unclear. In the present study, two F populations, derived from 1742 (white flesh) × FJ3211 (green flesh) and J16 (white flesh) × FJ5 (green flesh), were used to identify the green flesh ( ) locus. Genetic analysis revealed that the presence of green flesh was a quantitative trait that closely followed a normal distribution. Combining the results from QTL mapping and BSA-seq analysis, the locus was preliminarily determined to be located on chromosome 05 and was narrowed down to a 2.55-Mb interval by linkage analysis. A large J16 × FJ5 F population comprising 3,180 individuals was subsequently used to screen the recombinants, and the locus was fine-mapped to a region of 329.70 kb that harbors six genes. One of the candidate genes, , the zinc-finger transcription factor LOL1 (lsd one like 1 protein; ), was the strongest candidate gene for the locus according to sequence variation and expression analysis. Additionally, a point mutation (A > C) in resulted in the substitution of threonine (T) with proline (P) in the amino acid sequence, showing a complete relationship linked with flesh color in a panel of 45 germplasms. The study suggests that promotes the accumulation of chlorophyll content in chieh-qua and lead to green flesh. Our findings establish a theoretical and technical foundation for breeding different flesh color lines and elucidating the underlying mechanisms of flesh color in chieh-qua.